2020
DOI: 10.21608/ejmm.2020.249875
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti Toxoplasma antibodies in children with autism in Shebin Al-Kom district Menoufia Governorate, Egypt

Abstract: Background; Autism spectrum disorders (ASD), are a range of mental disorders of neurodevelopmental type. More than three billion human hosts are estimated to be affected by the protozoan parasite Toxoplasma gondii, which is intracellular pathogen with a particular preference for the central nervous system (CNS). Accumulating evidence suggests that latent chronic toxoplasmosis contributes to triggering and progression of many neurological and psychiatric disorders, however the link and prevalence in ASD is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In the present study, the incidence of toxoplasmosis among autistic children was 24.4% (11 participants) when compared to 22.2% (10 participants) in the control children, and the difference was not statistically significant. This finding is consistent with previous reports of a non-significant correlation between autism and Toxoplasma infection in Iran (Afsharpaiman et al 2014 ), Turkey (Esnafoglu et al 2017 ), and Egypt (Gouda and Shafey 2020 ). In contrast, other research demonstrated a significant relationship between autism and Toxoplasma infection in Egypt (Prandota et al 2015 ), Saudi Arabia (AL Malki et al 2021 ), and Iraq (Bazzaz and Jameel 2022 ), which was also supported by a meta-analysis reported from different countries (Nayeri et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the incidence of toxoplasmosis among autistic children was 24.4% (11 participants) when compared to 22.2% (10 participants) in the control children, and the difference was not statistically significant. This finding is consistent with previous reports of a non-significant correlation between autism and Toxoplasma infection in Iran (Afsharpaiman et al 2014 ), Turkey (Esnafoglu et al 2017 ), and Egypt (Gouda and Shafey 2020 ). In contrast, other research demonstrated a significant relationship between autism and Toxoplasma infection in Egypt (Prandota et al 2015 ), Saudi Arabia (AL Malki et al 2021 ), and Iraq (Bazzaz and Jameel 2022 ), which was also supported by a meta-analysis reported from different countries (Nayeri et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, there was a higher significant Toxoplasma seropositivity in boys than in girls in both the autistic and control groups, which was similar to sex distribution in past studies (Prandota et al 2015 ; Esnafoglu et al 2017 ). However, Gouda and Shafey ( 2020 ) have reported that autistic girls were more affected by Toxoplasma than boys, which can be explained by several reasons. For instance, according to Kang et al ( 2004 ), the immune response differs across gender in adolescents.…”
Section: Discussionmentioning
confidence: 99%